2020
DOI: 10.3390/molecules25245905
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nutraceuticals in COVID-19 Mediated Liver Dysfunction

Abstract: COVID-19 is known as one of the deadliest pandemics of the century. The rapid spread of this deadly virus at incredible speed has stunned the planet and poses a challenge to global scientific and medical communities. Patients with COVID-19 are at an increased risk of co-morbidities associated with liver dysfunction and injury. Moreover, hepatotoxicity induced by antiviral therapy is gaining importance and is an area of great concern. Currently, alternatives therapies are being sought to mitigate hepatic damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 154 publications
0
8
0
Order By: Relevance
“…Available studies suggest that MD exerts protective effects on the expression of several proatherogenic genes, resulting in modulation of vascular inflammation, thrombosis, and foam-cell formation[ 32 - 34 ]. In this sense, legumes, for which we demonstrated that patients with lower CV risk have a higher adherence, contain a lot of phytochemicals endowed with useful biological activities[ 35 , 36 ]. Phytochemicals were shown to have prominent antioxidant activity, improve endothelial function by increasing nitric oxide bioavailability and prevent atherosclerosis progression by inhibition of low-density lipoprotein oxidation[ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available studies suggest that MD exerts protective effects on the expression of several proatherogenic genes, resulting in modulation of vascular inflammation, thrombosis, and foam-cell formation[ 32 - 34 ]. In this sense, legumes, for which we demonstrated that patients with lower CV risk have a higher adherence, contain a lot of phytochemicals endowed with useful biological activities[ 35 , 36 ]. Phytochemicals were shown to have prominent antioxidant activity, improve endothelial function by increasing nitric oxide bioavailability and prevent atherosclerosis progression by inhibition of low-density lipoprotein oxidation[ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lupin, salvia, garlic, and EVOO have anti-oxidant, anti-inflammatory, or antiviral properties and can recover the expression of ACE2 on the cell membrane, otherwise suppressed by SARS-CoV-2 binding and entry into the cytoplasm. Sikander et al [ 6 ] provided information and summarized the effects of natural bioactive antiviral, immunomodulatory, and hepatoprotective nutraceuticals ( Silybum marianum , Solanum nigrum , Cichorium intybus , Allium sativum , Glycyrrhiza glabra , Phyllanthus amarus , Withania somnifera , Curcuma longa , and other hepatoprotective agents) that might be explored in managing COVID-19-induced liver dysfunction. Additionally, omega-3 long-chain polyunsaturated fatty acids (omega-3 LC-PUFAs) might also have effects on different stages of viral infection, including virus entry and replication, and help improve the inflammatory balance.…”
Section: Nutrition Therapy For Covid-19-related Liver Dysfunctionmentioning
confidence: 99%
“…Curcuma longa and Solanum Nigrum being hepato-protective, have been exploited as nutraceutical sources ( Sikander et al, 2020 ). Synergistic responses of combined nutraceuticals are also being studied, such as curcumin combined with quercetin and nobiletin metabolite, which shows enhanced anticancer effects ( DiMarco-Crook et al, 2020 ; Sharma et al, 2019 ).…”
Section: The Contemporary Global Market Of Nutraceuticalsmentioning
confidence: 99%